2019
DOI: 10.1080/19490976.2019.1697148
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic bacteria as modulators of cellular senescence: emerging concepts and opportunities

Abstract: Probiotic bacteria are increasingly gaining importance in human nutrition owing to their multifaceted health beneficial effects. Studies have also shown that probiotic supplementation is useful in mitigating age-associated oxi-inflammatory stress, immunosenescence, and gut dysbiosis thereby promoting health and longevity. However, our current understanding of the process of aging suggests a strong interrelationship between the accumulation of senescent cells and the development of aging phenotype, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 124 publications
0
25
0
Order By: Relevance
“…On the other hand, an age-associated increase in the CD4+/CD8+ T cells ratio, and a gradual decline in NK cell numbers were observed, which did not appear to be influenced by EGCG. However, EGCG supplementation enhanced the expression of regulatory molecule CD69 on T cells in 18 months old animals which has also been reported for different natural molecules (Holderness etal (Sharma and Padwad, 2020c). In addition, polyphenols are being advocated as promising alternative to oligosaccharide-based prebiotics, and previous studies have shown that polyphenols can influence probiotic growth either directly or by suppressing the abundance of pathogenic bacteria (Sharma and Padwad, 2020d).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…On the other hand, an age-associated increase in the CD4+/CD8+ T cells ratio, and a gradual decline in NK cell numbers were observed, which did not appear to be influenced by EGCG. However, EGCG supplementation enhanced the expression of regulatory molecule CD69 on T cells in 18 months old animals which has also been reported for different natural molecules (Holderness etal (Sharma and Padwad, 2020c). In addition, polyphenols are being advocated as promising alternative to oligosaccharide-based prebiotics, and previous studies have shown that polyphenols can influence probiotic growth either directly or by suppressing the abundance of pathogenic bacteria (Sharma and Padwad, 2020d).…”
Section: Discussionmentioning
confidence: 57%
“…Tan et al 2019), and potential modulators of the gut microbiome may have anti-cellular senescence attributes (Sharma and Padwad, 2020c). In addition, polyphenols are being advocated as promising alternative to oligosaccharide-based prebiotics, and previous studies have shown that polyphenols can influence probiotic growth either directly or by suppressing the abundance of pathogenic bacteria (Sharma and Padwad, 2020d).…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing awareness of the benefits of prophylactic use of probiotics in maintaining health and improving quality of life in the elderly population [ 33 , 34 , 35 , 36 ]. As summarized in Table 1…”
Section: Current Status Of Efforts On Geroscience Globallymentioning
confidence: 99%
“…Advancements in geroscience make us wonder whether certain probiotics might target basic biological mechanisms of aging. If such mechanisms can be validated, those probiotics could possibly be used to delay the onset of multiple age-related chronic diseases and thus effectively expand the health span [ 33 ].…”
Section: Probiotics For Anti-aging Reported From Research Modelsmentioning
confidence: 99%
“…Gut microbial communities of children, adults, the elderly, and centenarians have been found to cluster apart from one another other [ 12 , 13 ], suggesting that the gut microbial communities may in fact play different roles throughout the aging process. The development of age-related diseases is often associated with gut dysbiosis, changes in the gut microbiota that negatively impact host health [ 14 , 15 ]. Furthermore, aging is typically associated with decreased diversity and Firmicutes to Bacteroides ratio, as well as an increase in some Proteobacteria, opportunistic species, and pathobionts [ 12 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%